2023
DOI: 10.1093/rb/rbad012
|View full text |Cite
|
Sign up to set email alerts
|

Unique regulation of TiO2 nanoporous topography on macrophage polarization via MSC-derived exosomes

Abstract: The comprehensive recognition of communications between bone marrow mesenchymal stem cells (bm-MSCs) and macrophages in the peri-implant microenvironment is crucial for implantation prognosis. Our previous studies have clarified the indirect influence of Ti surface topography in the osteogenic differentiation of bm-MSCs through modulating macrophage polarization. However, cell communication is commutative and multi-directional. As the immune regulatory properties of MSCs have become increasingly prominent, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Furthermore, Wang et al discovered that the alteration in the diameter of micropatterned nanotubes also affected the polarization direction: macrophages on small diameter(30nm) nanotubes were more inclined to M2 polarization, and those on large diameter(100nm) nanotubes had the opposite results 281 . Similar conclusion was obtained by using Ti nanotubes with diameters of 80-100nm 290 . And by blocking the secretion of MSCs exosomes, it was concluded that M1 polarization was regulated by the paracrine pathway of MSCs.…”
Section: Perspectives On Current Understandingsupporting
confidence: 84%
“…Furthermore, Wang et al discovered that the alteration in the diameter of micropatterned nanotubes also affected the polarization direction: macrophages on small diameter(30nm) nanotubes were more inclined to M2 polarization, and those on large diameter(100nm) nanotubes had the opposite results 281 . Similar conclusion was obtained by using Ti nanotubes with diameters of 80-100nm 290 . And by blocking the secretion of MSCs exosomes, it was concluded that M1 polarization was regulated by the paracrine pathway of MSCs.…”
Section: Perspectives On Current Understandingsupporting
confidence: 84%
“…differentiation through autophagy. The nano surfaces with different dimensions have been prepared by anodization, which is a well-documented technique with excellent biocompatibility as previously reported [13,23]. From the proteomic analysis, autophagy was top enriched as KEGG enrichment analysis in the comparison between nano and smooth surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, another study demonstrated that the TiO 2 nanoporous topography promoted MSC-Exo to play an immunomodulatory role by inducing the M1 polarization of macrophages, potentially having a detrimental impact on the osteogenesis process. 157 Furthermore, the stiffness of the extracellular matrix (ECM) also mattered. Excessive ECM deposition in the tumour microenvironment may lead to an increase in substrate hardness, thereby promoting the secretion and modulating the biological behaviours of exosomes derived from cancer cells.…”
Section: Intrinsic Physical Properties (Substrate Topography and Stif...mentioning
confidence: 99%